Mr. Mercedes [compact disc, unabridged] : a novel - King, Stephen, 1947- (Simon & Schuster Audio, 2014)
Bill Hodges is bumping around, barely registering his retirement, when a maniac in a stolen Mercedes repeatedly drives into a line of unemployed folks waiting in the gray dawn of a gray Midwestern city for a job fair to open. Eight people are killed and 15 injured. Hodges immediately enlists two allies to help him find the killer, who so loved his little taste of death that he's planning to blow up thousands.